Cartilaginous Choristoma of Tonsil: A hidden clinical entity - Gautam, N.; Makaju, R.; Basnet, D.; Lama, B.; Maharjan, P. B. (Kathmandu University Medical Journal, 2021)
Choristoma is a tumor like mass which is an ectopic rest of normal tissue due to embryological developmental defect. The presence of choristoma in tonsil is extremely rare. On histopathological examination, mature hyaline cartilage were found surrounded by lymphoid follicles. We present a case of cartilaginous choristoma with the complaint of recurrent tonsillitis.